Potential, Capacity and Development of Hired Labor in Smallholding Rubber Production System: Lesson Learned from Traditional Rubber Area, Songkhla Province - Somboonsuke, Buncha; Dhammasaccakarn, Wanchai; Cherdchom, Parinya; Longpichai, Onanong; Phitthayaphinant, Purawich (Kasetsart Journal of Social Sciences, 2015)
This study investigated the dynamics, conditions of using hired labor, working characteristics, wages of hired labor, and guidelines for increasing the working efficiency of the hired labor of rubber farmer households in Songkhla province. A total sample of 395 rubber smallholding households that used hired labor was used for data collection through structured interviews. Also, 60 households of the total sample were used for in-depth interviews. Descriptive statistics were used for data analysis. The results classified the dynamics of hired labor into 5 periods; (1) before 1960: traditional rubber production, (2) 1961-1980: green revolution, (3) 1981-1992: alternative agriculture, (4) 1993-2002: initial industrial rubber production, and (5) 2003 to present: industrial rubber production. There was an increase in hired labor in rubber production with more complications in the hired labor process. There were 5 types of hired labor according to the sources of labor: relatives as hired labor, villagers as hired labor, different district or province hired labor in the south, different farmer households had a tendency to hire more tapping labor. This would affect the benefits of sharing between owners and hired laborers that could be divided into 3 patterns of: contract agreement, daily wage paid, and wage paid by activity. In the contract agreement, benefit ratios between owners and hired laborers were 60:40, 55:45, 50:50, and 70:30. Choosing a benefit ratio would depend on: (1) the skill and experience of the hired labor in working in rubber plantations, (2) the number of household laborers, (3) local wage rates and contract agreement characteristics, (4) farm size holding and labor capacity, (5) the impact of socio-economics, environment, policy, and politics, and (6) the frequency of tapping to increase family income when there was a high rubber price. The guidelines for the development of hired labor in the rubber production system were: (1) strengthening the socio-economic status of hired labor, (2) promoting relationships between owners and hired labor, (3) improving the bio-physical characteristics of the rubber plantation area, (4) promoting fair conditions and a contract agreement of benefits, (5) improving labor quality, and (6) increasing the skill of tapping and working hired labor through knowledge transfer and training processes.